FORMAREA APTITUDINILOR MATEMATICE LA ELEVII SUPRADOTAŢI - USM ADMIN (Moldova State University, 2009)
The primary aim of this article is to mark out the factors which form the children's mathematical abilities, to accentuate and to explain the physical capabilities of the students, which in the same conditions of load and educative opportunities, give different results in the mathematical activities.